Treatment of Advanced Retinoblastoma in Children Evacuated from Low-Income Countries: Experience from a National Referral Center in Portugal - Castela, Guilherme (2021)
Objective: The aim of our study was to characterize the evacuated African patients diagnosed with retinoblastoma and referred to the Portuguese national referral center (Centro Hospital e Universitário de Coimbra, University of Coimbra), identifying inequalities in the stage of diagnosis and prognostic results. Design: Retrospective observational study of evacuated African patients diagnosed with retinoblastoma and referred to the Portuguese National Referral Center (Centro Hospital e Universitário de Coimbra, University of Coimbra). Results: The study included 15 patients between October 2015 and October 2020 from Angola, Cape Verde, Guinea-Bissau and São Tomé and Príncipe. Seven (46.7%) children presented bilateral retinoblastoma. The median age at the time of diagnosis was 20.9 (interquartile range, 16–41) months. The presenting symptoms were leukocoria (86.7%), strabism (53.3%) and buphthalmus (40%). In terms of tumor staging, five (33.3%) children presented with extraocular retinoblastoma and 10 (66.7%) children presented with intraocular retinoblastoma. At presentation, no pineal involvement was diagnosed but two (13.3%) children presented with central nervous system involvement at the time of the first observation. Children were treated with enucleation, exenteration, systemic chemotherapy, intraarterial chemotherapy and/or supportive palliative care. During the follow-up period (mean 27.2 ± 18.2 months), the overall survival was 73.3%. Conclusion: A small proportion of African children are being referred to our center, when considering the expected incidence of retinoblastoma in these countries, and referred children arrive at advanced stages of the disease, compromising treatment outcomes. Considering retinoblastoma is now a curable disease, national and international interventions are required to attempt a better management of children born in low-income countries.